Cytotoxicity and the effect of cationic peptide fragments against cariogenic bacteria under planktonic and biofilm conditions - Kreling, Paula Fernanda [UNESP]; Aida, Kelly Limi [UNESP]; Massunari, Loiane [UNESP]; Caiaffa, Karina Sampaio [UNESP]; Percinoto, Célio [UNESP]; Bedran, Telma Blanca Lombardo [UNESP]; Spolidorio, Denise Madalena Palomari [UNESP]; Abuna, Gabriel Flores; Cilli, Eduardo Maffud [UNESP]; Duque, Cristiane [UNESP] (Taylor & Francis, 2016)
This study evaluated the cytotoxicity and effect of fragments derived from three oral cationic peptides (CP): LL-37, D6-17 and D1-23 against cariogenic bacteria under planktonic and biofilm conditions. For cytotoxicity analysis, two epithelial cell lines were used. The minimum inhibitory concentration and the minimal bactericidal concentration were determined for the CP fragments and the control (chlorhexidine-CHX) against cariogenic bacteria. The fractional inhibitory concentration was obtained for the combinations of CP fragments on Streptococcus mutans. Biofilm assays were conducted with the best antimicrobial CP fragment against S. mutans. The results indicated that D6-17 was not cytotoxic. D1-23, LL-37 and CHX were not cytotoxic in low concentrations. D1-23 presented the best bactericidal activity against S. mutans, S. mitis and S. salivarius. Combinations of CP fragments did not show a synergic effect. D1-23 presented a higher activity against S. mutans biofilm than CHX. It was concluded that D1-23 showed a substantial effect against cariogenic bacteria and low cytotoxicity.
Keywords: Biofilms; Cell culture; Dental caries; Peptides